Purchase order for supply & installation of suspended ceiling in the ground floor at 40 ft. height for the BRACU new campus project - Brac University (Brac University, 2023)
This purchase order has been made between Brac University and Sthapotto for supply and installation of suspended ceiling for Brac University new campus project.